2022
DOI: 10.1080/2162402x.2022.2096535
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori serology is associated with worse overall survival in patients with melanoma treated with immune checkpoint inhibitors

Abstract: The microbiome is now regarded as one of the hallmarks of cancer and several strategies to modify the gut microbiota to improve immune checkpoint inhibitor (ICI) activity are being evaluated in clinical trials. Preliminary data regarding the upper gastro-intestinal microbiota indicated that Helicobacter pylori seropositivity was associated with a negative prognosis in patients amenable to ICI. In 97 patients with advanced melanoma treated with ICI, we assessed the impact of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…They further observed that this negative impact seemed to occur independently of fecal microbiome composition. 16 Finally, a smaller cohort of 77 patients with advanced gastric cancer (34 H. pylori- positive and 43 negative individuals) also demonstrated inferior PFS and OS outcomes for H. pylori- positive individuals. 17 …”
Section: Discussionmentioning
confidence: 95%
“…They further observed that this negative impact seemed to occur independently of fecal microbiome composition. 16 Finally, a smaller cohort of 77 patients with advanced gastric cancer (34 H. pylori- positive and 43 negative individuals) also demonstrated inferior PFS and OS outcomes for H. pylori- positive individuals. 17 …”
Section: Discussionmentioning
confidence: 95%
“…Immunotherapy: Recent studies have shown that HP infection can adversely affect the tumor immune microenvironment and tumor immunotherapy. The overall survival (OS) and progression-free survival (PFS) of HP-positive cancer patients treated with immune checkpoint inhibitors, such as gastric cancer, melanoma and non-small cell cancer patients, were significantly reduced ( Che et al., 2022 ; Oster et al., 2022b ; Tonneau et al., 2022 ), but the specific mechanism is unknown. Some scholars have suggested that HP may reduce the efficacy of immunotherapy by changing the composition of intestinal flora and tumor immune microenvironment, affecting tumor immune response, but there is still a lack of relevant direct evidence ( Oster et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“… 7 Interestingly, previous research suggested that H. pylori infection is correlated with a favourable outcome in GC patients. 270 272 However, recent studies have indicated that the presence of H. pylori may affect the efficacy of ICIs in melanoma, 273 NSCLC, 274 and advanced GC, 275 introducing a new paradox regarding the varied effects of the same microorganism on cancer occurrence, prognosis, and treatment efficacy. Fungi also play a role in immunotherapy response in metastatic melanoma, with the Cladosporium genus significantly enriched in non-responders.…”
Section: Prognostic Role Of Intratumoural Microbiotamentioning
confidence: 99%